THE RELATIONSHIP OF THE ROLE OF POSYANDU cadres ON THE QUALITY OF LIFE OF ELDERLY STROKE PATIENTS IN THE WORK AREA MEURAH MULIA NORTH ACEH HEALTH CENTER - Nadia Ulfa; Regina Rahmi (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The increase in the number of elderly (elderly) in Indonesia is estimated to be the fastest growing elderly in the world. The increasing number of elderly cannot be separated from the aging process and its problems. One of the solutions made by nurses to improve the quality of life of the elderly is by carrying out health promotion to organize and provide nursing care for the elderly through elderly posyandu activities by optimizing health cadres. The results of an initial survey conducted by researchers through interviews of 10 elderly stroke patients, there were 6 elderly stroke patients who complained about their illness and their families also said the patients seemed not enthusiastic about living life because they lacked attention and lack of motivation from the surrounding environment, and 4 elderly stroke patients who accepts his illness gracefully and does not complain about his illness. The design of this study will use a cross-sectional type of analytic. The population in this study amounted to 32 people, namely all elderly stroke patients who were in the working area of the Meurah Mulia North Aceh Health Center. The sampling technique was carried out using the total sampling method, totaling 32 people. Data analysis was performed univariately and bivariately using the Chi Square test. Based on the results of the research conducted, it can be seen that there were 19 respondents (59.4%) in the Good category in terms of patient quality of life and 13 respondents (40.6%) in the less category. The results of statistical tests using the Chi Square Test obtained, value 0.002 <0.005, then Ho was rejected and Ha was accepted, so it can be concluded that there is a relationship between the role of Posyandu Cadres and the Quality of Life of Elderly Stroke Patients in the Working Area of the Meurah Mulia Health Center, North Aceh District.